(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Environment is equally as essential for human being as economics but there are many limitations which are connected with environment, when economy has given precedence over the environment problems which is having negative impacts on society. The environment is connected with the sustainable development as it is essential to preserve the human and also necessary to alter the attitude of the people for environment. Sustainable development has been portrayed as a connection between the environment, society and economy, therefore, these three cannot be studied as a distinct entity. The economics has given little bit importance when it comes to politics and at the same time environment problems has given lesser priority but this method is not appropriate in present situation as economy is directly linked with the society and human is dependent upon the environment. Thus, it is essential to have an analysis of these three distinct entities in a single frame and present paper’s strategy is to evaluate the dependencies of these three on one another. The future scope of the research is to take the initiative to preserve the environment from potential threats like climate change etc.